Optical coherence tomography in neurodegenerative disorders - CUNHA, Leonardo Provetti; PIRES, Leopoldo Antônio; CRUZEIRO, Marcelo Maroco; ALMEIDA, Ana Laura Maciel; MARTINS, Luiza Cunha; MARTINS, Pedro Nascimento; SHIGAEFF, Nadia; VALE, Thiago Cardoso (Arquivos de Neuro-Psiquiatria, 2022)
Structural imaging of the brain is the most widely used diagnostic tool for investigating neurodegenerative diseases. More advanced structural imaging techniques have been applied to early or prodromic phases, but they are expensive and not widely available. Therefore, it is highly desirable to search for noninvasive, easily accessible, low-cost clinical biomarkers suitable for large-scale population screening, in order to focus on making diagnoses at the earliest stages of the disease. In this scenario, imaging studies focusing on the structures of the retina have increasingly been used for evaluating neurodegenerative diseases. The retina shares embryological, histological, biochemical, microvascular and neurotransmitter similarities with the cerebral cortex, thus making it a uniquely promising biomarker for neurodegenerative diseases. Optical coherence tomography is a modern noninvasive imaging technique that provides high-resolution two-dimensional cross-sectional images and quantitative reproducible three-dimensional volumetric measurements of the optic nerve head and retina. This technology is widely used in ophthalmology practice for diagnosing and following up several eye diseases, such as glaucoma, diabetic retinopathy and age-related macular degeneration. Its clinical impact on neurodegenerative diseases has raised enormous interest over recent years, as several clinical studies have demonstrated that these diseases give rise to reduced thickness of the inner retinal nerve fiber layer, mainly composed of retinal ganglion cells and their axons. In this review, we aimed to address the clinical utility of optical coherence tomography for diagnosing and evaluating different neurodegenerative diseases, to show the potential of this noninvasive and easily accessible method.
Keywords: Tomography, Optical Coherence; Alzheimer Disease; Parkinson Disease; Multiple Sclerosis; Neurodegenerative Diseases; Amyotrophic Lateral Sclerosis; Retina